The Relationship Between The Parenting And Life Skill Application With The Cooking Interest At Budi Mulia Dua Elementary School Of Yogyakarta - Sumaiyah, Lathifah; M arwanti, M arwanti (Syntax Corporation Indonesia, 2024)
This study at Budi Mulia Dua Elementary School aims to find out (1) parenting done by parents (2) life skill application (3) children's cooking interest ( 4 ) the relationship between the parenting and the children's cooking interest (5) the reality between life skill application and the children's cooking interest at Budi Mulia Dua Elementary School (6) the reality ship between the parenting and life skill application and the children's cooking interest. The sampling technique uses proportional random sampling. The sample of research is Budi Mulia Dua Elementary School's students as many as 177 people. Methods of data collection using questionnaires. Data analysis techniques in this study use product moment correlation. The results of the study at Budi Mulia Dua Elementary School show that (1) parenting done by parents in good category with a percentage 42.3% (2) life skill application in good category with a percentage 40.6% (3) children's cooking interest in high category with a percentage 45.7% (4) the correlation between the parenting and the cooking interest is indicated by r observed = 0.917, ( 5) the correlation between life skill application and the cooking interest is indicated by r observed = 0.964, ( 6) the correlation between the parenting and life skill application with the cooking interest development is indicated used by double correlation r square = 0.923 compare r table = 0.148